Understanding the brain in health and disease: An interview with Karl Deisseroth, Professor of Bioengineering and Psychiatry at Stanford University - Schnapp, Esther (EMBO Rep, 2017)
Today, Karl Deisseroth was awarded the 4 million euro 2017 Else Kröner Fresenius Prize for his discoveries of optogenetics and of hydrogel‐tissue chemistry, and for developing circuit‐level insight into depression. We asked him how his and related work enhances our understanding of the brain and psychiatric diseases at the molecular level.